1982
DOI: 10.23986/afsci.72116
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experiments into the use of Streptomyces spp. isolated from peat in the biological control of soil and seed-borne diseases in peat culture 

Abstract: Streptomyces spp. isolates obtained from peat effectively inhibited the growth of Alternaria brassicicola Wiltshire, Fusarium culmorum (W. G. Smith) Sacc., F. sulphureum Schlechtendahl, Pythium debaryanum auct. non Hesse and Rhizoctonia solani Kühn on PDA medium, but Streptomyces spp. isolates from fine sand soil were not effective against F. culmorum compared to the strains isolated from peat. Treatment of cauliflower seeds with Streptomyces spp. isolated from peat effectively controlled damping-off caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 3 publications
1
37
0
1
Order By: Relevance
“…A commercial product containing Streptomyces griseoviridis, Mycostop, was applied through the irrigation system to control important plant pathogens, such as F. oxysporum, Botrytis cinera and Alternaria brassicicola (Tahvonen, 1982a(Tahvonen, , b, 1993Tuomi et al, 2001). However, seeds treated with S. griseoviridis were not effective in the control of C. musae of banana.…”
Section: Discussionmentioning
confidence: 99%
“…A commercial product containing Streptomyces griseoviridis, Mycostop, was applied through the irrigation system to control important plant pathogens, such as F. oxysporum, Botrytis cinera and Alternaria brassicicola (Tahvonen, 1982a(Tahvonen, , b, 1993Tuomi et al, 2001). However, seeds treated with S. griseoviridis were not effective in the control of C. musae of banana.…”
Section: Discussionmentioning
confidence: 99%
“…This strain, originally isolated from light coloured Sphagnum peat (Tahvonen 1982a(Tahvonen , 1982b (Tahvonen 1982a(Tahvonen , 1982bTahvonen and Avikainen 1987). Streptomyces griseoviridis strain K61 is used in root dipping or growth nutrient treatment of eut flowers, potted plants, greenhouse cucumbers, and various other vegetables (Mohammadi and Lahdenpera 1992).…”
Section: Actinomycetes As Biocontrol Toolsmentioning
confidence: 99%
“…1987), Hafnia (Sneh 1981), Micromonospora (Filonow and Lockwood 1985), Pasteuria (Brown et al 1985;Stirling 1984), Pseudomonas (Burr et al 1978;Caesar and Burr 1987;Chen and Echandi 1984;Colyer and Mount 1984;Elad and Baker 1985;Ganesan and Gnanamanickman 1987), Rhizobum and Bradyrhizobacterium (Chakraborty and Purkayastha 1984), Serratia (Sneh 1981;Sneh et al 1985), Streptomyces (Doumbou et al 1998;Emmert and Handelsman 1999;Liu étal. 1995;Tahvonen 1982aTahvonen , 1982b and Xanthomonas (Chen et al 1987;Kwok et al 1987). As shown hère, biocontrol agents are not limited to a spé-cifie bacterial group; however, given the microbial diversity of agroecosystems, it is probable that the full spectrum of potentially effective strains has barely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the microbial activity, as measured by the fluorescein diacetate technique, was higher in the least decomposed light peat, demonstrating that this type of peat was able to support a high activity of microbial biomass (Boehm and Hoitink, 1992). Tahvonen (1982b) isolated antagonistic Trichoderma spp. and Gliocladium spp.…”
Section: Greenhouses Are Well Suited For Biological Controlmentioning
confidence: 99%